Religion, religiosity and communalism - Bidwai, Praful (Ed.); Mukhia,Harbans (Ed.); Vanaik,Achin (Ed.) (New Delhi, 1996)
In this anthology, academics, journalists and activists come together to explore several facets of India's communal problem its history, political settings and theoretical underpinnings. Distinctions as well as convergence between religion, religiosity and communalism are opened up to examination in an analytical perspective at one level and investigation in regional and local contexts at another. The thread that binds the anthology is a look at the problem as dynamic, rather than a given phenomenon: its dynamics would as well allow space for its resolution.
Keywords: Religion-an articles